Local near field assisted ablation of fused silica: An experimental and theoretical study - Jamali, Abdul Aleem; Witzigmann, Bernd; Morarescu, Rodica; Baumert, Thomas; Traeger, Frank; Hubenthal, Frank (Applied Physics A: Materials Science and Processing, 2013)
In this contribution we present recent experimental and theoretical results on local near-field assisted laser ablation. Along these lines, we have generated sub-diffraction sized nanostructures on fused silica substrates, exploiting the local near fields of highly ordered triangular gold nanoparticle arrays generated by nanosphere lithography. After preparation, the nanoparticle arrays were irradiated with a single 35 fs long laser pulse with a central wavelength of λ = 790 nm. The pulse energy was set to E = 3.9 μJ, resulting in a fluence well below the ablation threshold of the fused silica substrates. In addition, 3D electromagnetic simulations using a finite integration technique in time domain have been performed. The simulations demonstrate that indeed the local field in the vicinity of the tips of the triangular nanoparticles overcome the ablation threshold and easily explain the generated nanostructures. Most importantly, the simulations show, that higher order modes contribute to the ablation process. These modes cause ablation along the side edges of the nanoparticles. Finally, we demonstrate, that the optical properties of the triangular nanoparticles, which can be tuned by their morphology, are crucial parameters for the generation of the ablation structures.
CRIS-Team Scopus Importer:2021-06-11